A pure-conduction transient model for heat pipes via derivation of a pseudo wick thermal conductivity. (March 2020) - Ma, Mingyang; Liang, Wenfeng; Wang, Shumiao; Xie, Qilin; Qian, Dazhi; Bai, Zhongxiong; Zhang, Tao; Zhang, Rui
Highlights: A pseudo wick thermal conductivity ( PWTC ) for heat pipes was defined and derived. A vapor transfer factor complementary to the classical Figure of Merit was defined. A PWTC -based pure-conduction heat pipe transient model was developed and verified. A criterion for heat pipe isothermality was developed and verified. The new criterion proved to be more rigorous and accurate than the traditional one. Abstract: Heat pipes (HPs) are promising in advanced energy and power systems, and simulating their transient performances is of great importance. However, the existing elaborate transient models are too complex for engineering simulations, and there is a lack of comprehensive and accurate criteria for HP isothermality on which various simplified models depend. Based on an analogy between the pressure drop formula of vapor flow and the Fourier's law, a pseudo wick thermal conductivity ( PWTC ) of HPs was novelly defined and derived. A novel pure-conduction transient model and a novel criterion of isothermality for HPs were developed and verified by experimental results. PWTC was found to depend on both the physical properties of working mediums as well as the HP dimensions, and proportional to a vapor transfer factor ( VTF ). VTF characterizes the coupled heat transfer effect of the vapor flow and the phase-change, thus complementary to the classical Figure of Merit ( FOM ) in HP theory. VTF increases with increasing temperature, and so does PWTC . The startup of a sodium HP was accurately simulated with the pure-conduction model. The effect of free-molecular flow proves to be negligible in the transient model. The PWTC -based criterion of isothermality proved to be more rigorous and accurate than the traditional transition-temperature-based criterion. The isothermal characteristics of room-temperature HPs differ from that of high-temperature HPs. FOM s of water always counts, while FOM s of the alkali-metals are significant only when temperature exceeds certain thresholds determined by PWTC and the boundary conditions.The modeling and analyzing methods are of certain generality, and can be extended to evaluate the applicability of simplified models, to judge the isothermality, and to construct three-dimensional transient models of complex systems.